Performance Audit of National Rural Health Mission (NRHM) in Tripura (2011-2016) - CAG of India (CAG of India)
This performance audit of National Rural Health Mission in Tripura for the period 2011-2016 revealed that the State Government did not conduct household surveys to identify the local needs of health care. Village Health Action Plans were not prepared. Lack of proper assessment by the State Health Society (SHS) led to short release of Rs 273.46 crore by Government of India (GoI). Even out of the funds provided by GoI, SHS could utilise only 51 to 69 per cent during 2011-16. Rs 1.51 crore advanced to 116 officials was lying outstanding. The number of Sub Centres (SCs), Primary Health Centres (PHCs) and Community Health Centres (CHCs) were below the prescribed level by 12, 47 and 56 per cent respectively in the State. In the three test checked districts, there was a shortage of SCs, PHCs and CHCs by 11, 42 and 53 per cent respectively. 69.57 per cent test checked SCs were running without water supply and electricity and 34.78 per cent without toilets. There were no specialists in CHCs and Sub Divisional Hospitals. In 279 SCs there was no Auxiliary Nursing Midwife/Female health worker. Four test checked CHCs did not have facilities for Caesarean Section delivery and none of the 23 test checked SCs had facilities for institutional delivery. Although there was a high prevalence rate of Anaemia amongst pregnant women (54.4 per cent) in the State, 36 per cent of pregnant women did not receive three Ante Natal check ups, and 40 per cent did not receive 100 Iron & Folic Acid tablets. State Quality Assurance Committee had not met even once till June 2016. Internal assessment and patient satisfaction survey was not done in any of the test checked facilities. Health Management Information System lacks data integrity. Hence internal control, supervision and monitoring were inadequate.
For the Period 2011-12 to 2015-16